Transformative Transdisciplinary Approaches to Digitalisation in the Tourism Supply Network: Enhancing Resilience and Collaboration in Gauteng and KwaZulu-Natal - Portia Pearl Siyanda Sifolo (Tourism and Hospitality)
Stakeholder fragmentation in transdisciplinary research often impedes innovation in South Africa’s tourism sector. The real-time supply network for MSMEs in Gauteng and KwaZulu-Natal struggles with digital adoption, limiting its resilience despite rising demand in the digital economy. This study examined how a transdisciplinary approach can enhance the Tourism Supply Chain Network in these regions—an urban hub (Gauteng) and a coastal cultural destination (KwaZulu-Natal)—to unlock their potential. Employing action research, this study engaged stakeholders (tourism operators, tech developers, and communities) to co-create data-driven digital solutions, including a real-time supply network. The collected data included both qualitative insights from workshops and interviews, as well as quantitative metrics such as platform usage and tourist engagement, which were analysed using descriptive statistics. Innovative technologies improved the supply chain efficiency, cutting coordination delays by 25% in Gauteng and boosting rural tourism visibility in KwaZulu-Natal, with a 30% increase in bookings. Gauteng saw urban connectivity gains, while KwaZulu-Natal achieved inclusive growth. This study provides a scalable, data-driven framework for digitalisation in tourism supply networks, offering practical strategies for stakeholders. It advances innovative technologies in emerging markets, emphasising the transformative potential of transdisciplinary collaboration to build resilient, collaborative tourism ecosystems in South Africa.